The prospect of microbial oils production from oil palm empty fruit bunch - Ahmad, Farah; Zhang, Zhanying; Doherty, William O. S.; O’Hara, Ian M. (2017)
Oil palm empty fruit bunch (EFB) is a lignocellulosic biomass and has the potential to be converted into oil that can be used as the feedstock for biodiesel production. The production of microbial oil from EFB can be performed through biochemical routes of cultivating oleaginous microorganism on EFB hydrolysates. Oleaginous microorganisms, including microalgae, yeasts and fungi, accumulate oils from carbon substrates assimilation, within its cell membrane, typically under nitrogen-limiting conditions. This paper aims to explore the feasibility of producing microbial oil production from EFB and other oil palm biomas. Most studies on the production of microbial oil from lignocellulosic biomass were performed using yeasts and fungi. Mucor plumbeus fungi was shown to be promising for EFB-derived oil production. The outlook of producing microbial oil and biodiesel from EFB was evaluated through previous techno-economic studies. Microbial oil has potential to supplement palm oil industry with cheaper feedstock cost. Microbial oil production from oil palm biomass could be integrated into palm oil industry, via the production of biodiesel from non-food feedstock and oleochemicals manufacturing. The proposed integration concept can potentially improve the sustainability and profitability of the palm oil industry.